(untitled) (Research, Society and Development, 2020)
This work consists of the study of methomyl removal, an extremely toxic carbamate pesticide, contained in aqueous solutions synthesized, by adsorption in residual orange bagasse from industrial juices processing. The adsorption kinetics was studied by obtaining the best fit for the model of pseudo-second order (R2= 0.949). The Langmuir isotherm model adjusted better to the experimental data confirming the adsorption in monolayers, without interaction among the adsorbate molecules. The scanning electron microscopy (SEM) revealed that particulate adsorbents have rather irregular surface, but with rigid structure and virtually no internal pores. The characterization of the functional groups by infrared spectroscopy (FTIR) revealed the presence of hydroxyl, Carbonyl and carboxylic groups on the adsorbents particles surface. Central composite rotational design 2x2 (DCCR 2x2) was used for the statistical study of the effects of pH and solid/liquid ratio (R) on the methomyl adsorption capacity in orange bagasse particles. The obtained mathematical model adjusted well to the experimental data (R2= 95%). In the studied intervals the highest values of adsorption capacity (q) were 3.73 and 3.43 (mg.g-1), obtained under the conditions of pH 6.0 with R 0.017 g.mL-1 and pH 4.5 with R 0.015 g.mL-1, respectively. Thus, it was possible to conclude that there was a greater adsorption in assays containing greater adsorbent mass in pH slightly acid.